2014
DOI: 10.5539/ies.v7n13p219
|View full text |Cite
|
Sign up to set email alerts
|

Vocabulary Learning Strategies and Arabic Vocabulary Size among Pre-University Students in Malaysia

Abstract: Vocabulary learning strategies and vocabulary size are among the main factors that help determine how students learn second language vocabulary. The present study was an attempt to exploring the relationship between vocabulary learning strategies and Arabic vocabulary size of 742 pre-university in Religious High School (SMKA) and Government-Aided Religious School (SABK). TAV test and Schmitt's (1997) vocabulary learning strategies questionnaire including 5 categories (Determination, Social, Memory, Cognitive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 21 publications
1
24
0
3
Order By: Relevance
“…The relationship was on determination strategy, social strategy, memory strategy, and metacognitive strategy. This is also in line with Baharudin and Ismail (2014) whose findings of the study revealed that there was a relationship between the use of vocabulary learning strategies of students and their Arabic vocabulary size. Several other studies also confirmed that relationship exists between vocabulary learning strategy used by students and their vocabulary mastery, in this case students' vocabulary size (Komol and Sripetpun, 2011;Boonkongsaen and Intaraprasert, 2014;Mokhtar, 2009).…”
Section: Influence Of Students' Vocabulary Learning Strategies On Thesupporting
confidence: 90%
“…The relationship was on determination strategy, social strategy, memory strategy, and metacognitive strategy. This is also in line with Baharudin and Ismail (2014) whose findings of the study revealed that there was a relationship between the use of vocabulary learning strategies of students and their Arabic vocabulary size. Several other studies also confirmed that relationship exists between vocabulary learning strategy used by students and their vocabulary mastery, in this case students' vocabulary size (Komol and Sripetpun, 2011;Boonkongsaen and Intaraprasert, 2014;Mokhtar, 2009).…”
Section: Influence Of Students' Vocabulary Learning Strategies On Thesupporting
confidence: 90%
“…In addition, Nik Mohd Rahimi et al (2010); Harun & Zawawi (2014) found out that Arabic language teaching and learning will fail to achieve the desired curriculum goal because of the poor vocabulary acquisition among students. These problems have contributed to the declining performance of Arabic language examination at school and national levels as reported in the study.…”
Section: Issues and Problemsmentioning
confidence: 99%
“…While Rosni (2013) and Harun & Zawawi (2014) believed that the teaching and learning of Arabic vocabulary should be given a serious attention by all parties in order to improve the performance of students in examinations. In addition, the size and depth of vocabulary acquired greatly influence the examination achievement Arabic.…”
Section: Reflections and Suggestions: Experience 3 (Examination)mentioning
confidence: 99%
See 1 more Smart Citation
“…One of the factors that distinguish the level of foreign language achievement of a student is Language Learning Strategy (LLS) used. The studies about LLS in Malaysia have found a significant relationship between the use of LLS with skills and mastery of the language (Baharudin & Ismail, 2014;Nurazan, 2004;Teh, Yusoff, Embi, & Mahamod, 2000). The study done by Mahamod & Embi (2005) which focuses on the use of Language Learning Strategy among brilliant students and weak students in mastering English Language reading finds that the excellent students use more LLS in order to enhance their language skills compared to weak students.…”
Section: Introductionmentioning
confidence: 99%